2021
DOI: 10.1017/s0954579421000948
|View full text |Cite
|
Sign up to set email alerts
|

Applying new RDoC dimensions to the development of emotion regulation: Examining the influence of maternal emotion regulation on within-individual change in child emotion regulation

Abstract: While the Research Domain Criteria (RDoC) acknowledges that environmental and developmental influences represent important elements of the RDoC framework, there is little specificity regarding how and when to systematically examine the impact of these dimensions on domains of function. The primary aims of this paper are to demonstrate the ways in which the RDoC can be expanded to include an explicit emphasis on (a) assessing within-individual change in developmental processes over time and (b) evaluating the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 106 publications
1
9
0
Order By: Relevance
“…These findings also provide further support for theories proposing both direct and indirect relations between parent and child ER difficulties (see Byrd et al, 2021; Morris et al, 2007). Specifically, findings revealed a direct relation between mother and adolescent ER difficulties and an indirect relation through maladaptive maternal responses to children’s emotional distress (i.e., maladaptive emotion socialization).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…These findings also provide further support for theories proposing both direct and indirect relations between parent and child ER difficulties (see Byrd et al, 2021; Morris et al, 2007). Specifically, findings revealed a direct relation between mother and adolescent ER difficulties and an indirect relation through maladaptive maternal responses to children’s emotional distress (i.e., maladaptive emotion socialization).…”
Section: Discussionsupporting
confidence: 80%
“…GRATZ, MYNTTI, KIEL, KURTZ, AND TULL 6 emphasizing both the relevance of parental modeling of maladaptive ER to children's ER difficulties (Byrd et al, 2021;Morris et al, 2007) and the key role of maternal responses to children's emotional distress in children's development of ER (Eisenberg et al, 1998(Eisenberg et al, , 2010Morris et al, 2007). In particular, findings of an indirect relation of maternal ER difficulties to adolescent ER difficulties through maladaptive maternal emotion socialization are consistent with the premise that mothers who struggle with their own ER may have difficulties accepting or tolerating their children's negative emotional expressions, leading to attempts to quickly downregulate such emotional expressions through punishment or minimization (Byrd et al, 2021;Kiel et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings highlight the significance of integrating these factors into etiological models of aggression and underscore potential treatment implications. For example, research demonstrates that targeting maternal ER improves parenting behaviors (Martin, Roos, Zalewski, & Cummins, 2017;Zalewski, Lewis, & Martin, 2018), and our own preliminary work in this sample has demonstrated that treatment-driven improvements in maternal ER difficulties has indirect effects on child externalizing symptoms 1 year later (Byrd, Lee, Frigoletto, Zalewski, & Stepp, 2021). Moreover, emerging work suggests that targeting maternal ER in combination with maternal validation training may further enhance child outcomes (Havighurst & Kehoe, 2017;Highlander et al, 2022), and our data suggest that maternal validation training for mothers with ER difficulties may be especially indicated when their children show heightened physiological reactivity to frustration.…”
Section: Discussionmentioning
confidence: 86%